Tea and tea products : chemistry and health-promoting properties - Ho, Chi-Tang , 1944-; Shahidi, Fereidoon , 1951-; Lin, Jen-Kun (Nutraceutical science and technology, 2009)
s including black, green, and oolong. It also discusses production and manufacturing aspects.